Actividad inhibitoria in vitro de corteza de Maytenus macrocarpa (Ruiz & Pav.) Briq., Erythrina fusca Lour y hojas de Calathea lutea Schult sobre α- glucosidasa - Ramírez Cárdenas, Christian Rafael (2023)
α-Glucosidase inhibitors slow the absorption of carbohydrates in the intestine and can be used in people with type 2 diabetes. The aim of the study was to determine the inhibitory activity of the bark of Maytenus macrocarpa (Ruiz & Pav.) Briq., Erythrina fusca Lour and Calathea lutea Schult leaves on α – glucosidase, evaluated at concentrations of 100, 250, 500 and 1000 µg/mL. The results showed that the bark of M. macrocarpa (Ruiz & Pav.) Briq. presented an inhibition greater than 50% at 1000 µg/mL; unlike the extracts of the bark of E. fusca Lour and leaves of C. lutea Schult. The inhibitory concentration (IC50) for bark of M. macrocarpa (Ruiz & Pav.) Briq. it was an IC50=935.00 µg; bark of E. fusca Lour and leaves of C. lutea Schult were not considered active; which allows us to conclude that the bark of M. macrocarpa (Ruiz & Pav.) Briq had the best inhibitory effect, so this species could be considered promising in the adjuvant treatment of type 2 diabetes.